Designing of putative siRNA against geminiviral suppressors of RNAi to develop geminivirus-resistant papaya crop - Saxena, Sangeeta; Kesharwani, Rupesh K; Singh, Vinayak; Singh, Sarita (International journal of bioinformatics research and applications, 2013)
Geminiviruses are single-stranded circular DNA viruses causing leaf curl disease in papaya crop. Post-Transcriptional Gene Silencing (PTGS), also known as RNAi, acts as a natural antiviral defence mechanism and plays a role in genome maintenance and development in plants. PTGS suppression by viruses makes the plant RNA silencing machinery inefficient. Three geminiviral genes namely AV2, AC2 and AC4 are found to play the role in suppression of RNA silencing. siRNA degrades the target mRNA in a homology-dependent manner. In-silico designing of siRNA against these three genes of geminiviruses infecting Carica papaya was done using bioinformatics tools. This strategy may provide PTGS by specifically targeting the viral genes involved in suppression of plant RNA silencing machinery.